Exploring the Links Between Student and Classmate Chronic Absenteeism. Issue 12 (December 2020) - Gottfried, Michael A.; Kirksey, J. Jacob; Ozuna, Christopher S.
Background: In efforts to address chronic absenteeism, educational stakeholders have begun to focus on which school factors might link to how and if students miss school. One underexplored area within school is the context of the classroom and, namely, the spillover effects of peers. This study examined whether students were more likely to be chronically absent when they had a chronically absent classmate. Research Questions: (1) In elementary school, does having chronically absent classmates in the fall influence individual students' absences in the spring of that same year? (2) Does this differ by the classroom proportion of chronically absent classmates? Subjects: This study used administrative data from an urban school district in California. The district consisted of 13 public elementary schools. From these schools, the analytic sample contained N = 14, 891 student observations from 2011 to 2014. Research Design: This study examined whether a student was more likely to be chronically absent in the spring semester of the school year if they had a chronically absent classmate in the fall. We employed linear probability models with multiple fixed effects and time-varying covariates. Errors were clustered at the classroom level. Findings: We found that students were more likely to be chronically absent in the spring when their classmates were absent in the fall. This finding was consistent across model specifications. Conclusions: This finding supports previous research, highlights the value of promoting fall attendance, and aligns with current national, fall-based attendance-boosting policies and programs. When taken together with the idea that absences affect not only the absent child, but also raise the chance of other students being absent, it becomes even more crucial for administrators and policymakers to make informed decisions to address chronic absenteeism.